2011
DOI: 10.1302/0301-620x.93b11.27309
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary and total femur replacement in revision arthroplasty as a last limb-saving option

Abstract: There has been a substantial increase in the number of hip and knee prostheses implanted in recent years, with a consequent increase in the number of revisions required. Total femur replacement (TFR) following destruction of the entire femur, usually after several previous revision operations, is a rare procedure but is the only way of avoiding amputation. Intramedullary femur replacement (IFR) with preservation of the femoral diaphysis is a modification of TFR. Between 1999 and 2010, 27 patients with non-onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Authors reporting the use of a megaendoprosthesis for TFR as a salvage procedure for periprosthetic disease included various indications, 8,9,[23][24][25] with 21% 25 to 41% 9 of reported cohorts sustaining Patients with a periprosthetic fracture represent a distinct subgroup of patients who may have had a well-functioning implant before their injury, and this was found in the current cohort, with a high physical component score on preinjury SF-12. The surgical goal for these patients is to return them to their preinjury functional status rather than to improve this status, and the current study showed that this can be achieved with TFR.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Authors reporting the use of a megaendoprosthesis for TFR as a salvage procedure for periprosthetic disease included various indications, 8,9,[23][24][25] with 21% 25 to 41% 9 of reported cohorts sustaining Patients with a periprosthetic fracture represent a distinct subgroup of patients who may have had a well-functioning implant before their injury, and this was found in the current cohort, with a high physical component score on preinjury SF-12. The surgical goal for these patients is to return them to their preinjury functional status rather than to improve this status, and the current study showed that this can be achieved with TFR.…”
Section: Discussionmentioning
confidence: 69%
“…These authors showed good functional results, according to the Harris Hip score, and these findings were comparable to other studies reporting the outcome of TFR for all-cause salvage of periprosthetic disease. 8,9,24 This series reported by Peters et al 23 was also retrospective, with no preinjury outcome scores available for comparison with postoperative results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total femoral replacement could have addressed the intercalary nonunion and provided the potential for immediate weight bearing. [9][10][11] One of the authors (HAC) has used this option in similar patients. However, to mitigate the risks of persistent infection, this would have been best performed as a staged procedure to follow placement of an antibiotic spacer and given this patient's age and the nature of her infection, she would have remained at high risk of a recurrence with few options for salvage of her limb.…”
Section: Discussionmentioning
confidence: 99%